The Relationship Between Understanding Science Concepts and Critical Thinking Skills of Elementary School Students - Az Zahra , Tiara Anggun; Wijanarko, Tiok (Journal of Educational Sciences, 2025)
Critical thinking skills are one of the four essential competencies required in the 21st century. One of the factors influencing critical thinking skills is the understanding of science concepts. This study aims to analyze the significant relationship between the understanding of science concepts and the critical thinking skills of elementary school students in Tujuah Koto Talago Village. A quantitative approach with a correlational research design was employed in this study. Research data were collected through written tests, consisting of multiple-choice questions to assess the understanding of science concepts and essay questions to evaluate critical thinking skills. Hypothesis testing was conducted using the Pearson Product Moment correlation method. The results indicate a correlation between the understanding of science concepts and students' critical thinking skills, as evidenced by a significance value of 0.001 < 0.05. Thus, it can be concluded that there is a significant relationship between the understanding of science concepts and the critical thinking skills of elementary school students in Tujuah Koto Talago Village.